The American West as a social-ecological region: drivers, dynamics and implications for nested social-ecological systems. (6th November 2019) - Jones, Kristal; Abrams, Jesse; Belote, R Travis; Beltrán, Bray J; Brandt, Jodi; Carter, Neil; Castro, Antonio J; Chaffin, Brian C; Metcalf, Alexander L; Roesch-McNally, Gabrielle; Wallen, Kenneth E; Williamson, Matthew A
Abstract: The American West exists in the popular imagination as a distinct region, and policies and politics often suggest that both the challenges and the opportunities for land management and human well-being across the region are relatively homogeneous. In this paper, we argue that there are key characteristics that define the West as a social-ecological region, and also that there are myriad social-ecological systems (SESs) within the region that require diverse and dynamic approaches to managing change over time. We first conceptualize aridity, topography, and a unique political economy of land as exogenous factors that persist over time and space to define the American West as a contiguous social-ecological region. We then identify a second set of characteristics that show high degrees of variation across SESs within the American West. Finally, we operationalize the relationships between regional characteristics and local dynamics through a set of case studies that exemplify specific types of SESs in the region. The results of these empirical representations of the regional and intra-regional social-ecological dynamics of the contemporary American West highlight the implications for research and management of taking a cross-scale integrated approach to address pressing social-ecological opportunities and challenges in complex adaptive systems.